High Performance Of Direct Torque Control For Five Phase Induction Machine - Victor Raj, Logan Raj Lourdes (UTeM, 2016)
In recent years, research on multiphase AC drives has received great attention due to its several advantages over three-phase drives such as reducing the amplitude and increasing the frequency of torque pulsations, reducing the rotor harmonic currents, reducing the current per phase without increasing the voltage per phase, and lowering the DC-link current harmonics and higher reliability. Until now, however, neither a circular flux operation nor a decagonal flux operation in formulating an optimal switching strategy has been proposed to achieve high-torque control performance of Direct Torque Control (DTC) of five-phase induction machines. A few previous studies on DTC of five-phase induction machine are limited to analyze the effects of selecting different voltage vectors on torque and flux control performances, which do not facilitate the DTC to obtain fast torque dynamic control, reduced torque ripple and switching frequency. This thesis proposes an optimal switching strategy of DTC of five-phase induction machines for high-performance torque control. By employing a five-phase inverter in the proposed method, it provides a greater number of voltage vectors as compared to that offered in the three-phase inverter which gives more options to select the most optimal voltage vectors. The analysis of effects of selecting different voltage vectors on DTC performances are carried out to identify the most optimal vectors that can be chosen to improve torque control performances for every operating condition. The identification is made with the aid of vector diagrams and some equations which are, equations of torque rate, slip angular frequency and current dynamic. Once the identification is done, all optimal vectors are tabulated into a look up table, and the optimal switching of vectors is accomplished by providing appropriate error status and flux sector into the look up table. The appropriate error status are obtained from the hysteresis comparators which are reponsible to determine proper amplitude of vectors and flux control operations, either to form the flux trajectory into a circular or a decagonal locus. The improvements of the proposed method are verified via simulation and experimental results. The results have shown that the torque ripple and switching frequency in the proposed method are greatly reduced about 50 % and 40 %, respectively from that obtained in the DTC with non-optimal switching strategyof five phase inverter, particularly at low-speed operation. The results have also showed that the proposed DTC with decagonal flux control produces a faster torque dynamic response than the non-optimal switching strategy of five phase inverter DTC. These improvements offered are important features for the electrical drive applications that require high-performance torque control and reduced switching losses or high-efficiency.